Daïnah la métisse Based on a Short Story by Pierre Daye - Daye, Pierre (Gaumont Vidéo, 2018)
We will probably never know what the original cut of "Daïnah la métisse" was like. Reduced by half before its release, Jean Grémillon’s film, despite his efforts, was turned into an oddity full of gaps, which paradoxically emphasize the beauty of this hour of dark poetry. We distractedly watch the exotic story imagined by Charles Spaak, a detective story behind closed doors with Shakespearean elements, but quickly lose ourselves in the film's hypnotic magic. You must board Grémillon's film as if entering a dream and venture forward incredulous through the ocean liner's furnishings, halls, bends and straight lines filmed with the geometric poetry of Dziga Vertov. Let yourself be pulled into a masked ball, a hallucinatory nightmare in which the lopsided portraits by Braque and Picasso seem to come to life. Blissfully admire a magician who lets his knife twirl in the air before vanishing in a cloud of smoke. And finally be enchanted and amazed by Daïnah, her white stole, her fantastic jewellery, her sensual, intense jazzy dancing, her cruise ship spleen. Daïnah is played by the mysterious Laurence Clavius, a mixed-race actress of unreal beauty. After just one film she disappeared, a fate similar to the film's, fleeting and elusive. Grémillon is an illusionist himself, inviting us on an unusual trip. His travel companions are Epstein, Dulac, Cocteau and Richter, and he left behind the producers who wanted to bring him back down to earth, now lost in the obscurity of their small careers. [festival.ilcinemaritrovato.it]
Keywords: Blu-Ray-Disc